Genetic Breakthroughs in Crop Resilience: Adapting to Climate Extremes - Hawayanti, Erni; Umali, Jamal (Assyfa Journal Scientific Essay, 2024)
Increasingly extreme climate changes have posed significant challenges to the global agricultural sector, particularly in maintaining productivity and food security amidst the rising frequency of droughts, floods, extreme temperatures, as well as pest and disease attacks. This research aims to identify and analyze the latest genetic breakthroughs that contribute to enhancing crop resilience against various stresses caused by climate change. By using the Systematic Literature Review (SLR) method, this article reviews the latest scientific literature from various leading databases, focusing on genetic innovations such as genome engineering (including CRISPR-Cas9), marker-based selection, and conventional breeding that have successfully increased plant tolerance to drought, high temperatures, and pathogen attacks. The results of the study indicate that the application of these genetic technologies can significantly stabilize crop yields under uncertain climate conditions, as well as strengthen food security and the sustainability of agricultural systems. In conclusion, the integration of genetic breakthroughs into plant breeding programs is crucial for building adaptive and resilient agricultural systems against climate change. However, its implementation requires cross-sector collaboration and support from policy and further research.